When is synthetic sufficient? Ethical considerations and alternatives in simulation-based ultrasound education - Andrea J. Doyle; Claire M. Condron (Advances in Simulation)
Abstract Simulation-based education (SBE) has become an integral part of training in health professions education, offering a safe environment for learners to acquire and refine clinical skills. As a non-ionising imaging modality, ultrasound is a domain of health professions education that is particularly supported by SBE. Central to many simulation programs is the use of animal models, tissues, or body parts to replicate human anatomy and physiology. However, along with its educational benefits, the use of animals in SBE generates a considerable amount of waste, raising important environmental and ethical concerns. Although research indicates that animal models yield comparable educational outcomes to synthetic models, animal models continue to be preferred in surgical and medical training. In response to these challenges, the principles of Replacement, Reduction, and Refinement (the 3Rs) have emerged as guiding standards to minimise the impact of animal use in research and education. Furthermore, synthetic models align with 3R principles, addressing ethical and environmental issues by reducing animal dependence and waste generation. Synthetic models offer key educational benefits over animal models by closely mimicking human anatomy and pathophysiology, providing consistent and anatomically accurate training. Unlike animal models, they eliminate variability in tissue properties, ensuring standardised and reliable experiences. Moreover, synthetic models can simulate specific pathologies, enabling targeted learning that may be difficult with animal tissue. Resistance related to clinical relevance and preference for animal-based SBE is a persisting challenge that might be overcome through the development of clinically and anatomically relevant tissue-mimicking materials, like those previously developed for other applications such as quality assurance phantoms in diagnostic imaging. The involvement of knowledge or end-user engagement, along with evidence-based design solutions, is crucial to catalyse a paradigm shift in a discipline deeply entrenched in tradition. The combined expertise, skills, and perspectives of medical professionals, educators, academic researchers, and industry specialists could collaboratively develop alternative methods to simulate live animal scenarios, replacing and reducing animal tissue dependence in SBE.